(untitled) (Scholars’ Journal, 2022)
Social marketing tends to use commercial marketing tools and strategies to change people’s behavior for the betterment of the individual. Social marketing campaigns are used to deliver messages tothe target groups. Social marketing campaigns disseminate information to the target groups to bring awareness about social causes or issues. The campaign provides messages to modify the knowledge, attitudes and behaviour of a large proportion of the population. This paper discusses the 8 Ps of social marketing mix (product, price, place, promotion, public, policy, partnership, and purse strings) and its application during the global pandemic of COVID-19. The comprehensive qualitative synthesis did of previously published information. The original research articles were extracted from google scholar in November 2021 by using search keywords “social marketing” OR “social marketing mix” AND“COVID-19” OR “ Coronavirus Disease 2019”. The study’s primary finding of this paper was that social marketing mix strategies (8 ps) had significantly applied to increase public awareness during the global pandemic of COVID-19. In addition, the research paper identifies some emerging areas for future research. The quantitative review techniques would be a valuable future extension such as systematic,bibliometric, and meta-analysis. This research paper offers an application of social marketing mix strategies to prevent such a pandemic and provides a guide for future research on social marketing mix.